Hemophagocytic lymphohistiocytosis due to disseminated histoplasmosis in a patient with HIV infection - Krishna Divyashree; Harpreet Singh; Mayur Parkhi; Indrani Karmakar; Man Updesh Singh Sachdeva; Vikas Suri; Ashish Bhalla (Journal of Global Infectious Diseases, 2023)
Hemophagocytic lymphohistiocytosis is usually considered a rapidly progressive fatal illness with poor outcomes. It is of two types: primary or familial and secondary. In patients with HIV, opportunistic infections are the secondary triggers of HLH. First line of management of infection associated HLH is treatment of the underlying infection. Here, we present a case of HLH in HIV infection due to disseminated histoplasmosis managed with liposomal amphotericin B, who required immunosuppressive therapy with intravenous immunoglobulin and dexamethasone due to nonresponse to primary therapy.